HUBUNGAN PEMAHAMAN TENTANG PENGAJARAN DOA DENGAN IMPLEMENTASI KEHIDUPAN DOA PRIBADI JEMAAT - Verayanti Verayanti; Soendoro Jahja; Sugeng Budi Suryanto (STT Kristus Alfa Omega, 2020)
Understanding the prayer is very important for every Christian, because prayer is a conversation, listening, telling all thoughts, feelings, doubts, problems, complaints, hopes, and joy with God. GBT Kristus Penebus Boyolali is one of the Pentecost-Charismatic churches that applies the discipline of prayer for their congregants. This research uses descriptive qualitative methods to explain the congregation's understanding of the prayers taught and how they apply them to their prayer life. In-depth interviews were conducted with ten respondents of the GBT Kristus Penebus Boyolali congregation who produced a good understanding of prayer but were still inconsistent in its application.